2016
DOI: 10.1136/heartjnl-2016-309983
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccine as a coronary intervention for prevention of myocardial infarction

Abstract: Cardiovascular disease (CVD) is the leading cause of morbidity and mortality globally. Influenza is one of the leading infectious causes of morbidity and mortality globally, and evidence is accumulating that it can precipitate acute myocardial infarction (AMI). This is thought to be due to a range of factors including inflammatory release of cytokines, disruption of atherosclerotic plaques and thrombogenesis, which may acutely occlude a coronary artery. There is a large body of observational and clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
98
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(111 citation statements)
references
References 46 publications
0
98
0
13
Order By: Relevance
“…Based on these data, use of these medications is likely to increase among cardiologists, and the coordination between cardiologists and PCPs when initiating and monitoring these medications will be critical. Additionally, influenza vaccination reduces the risk of secondary myocardial infarction in patients with CAD . However, this was the HEDIS measure with lowest achievement rates in our population.…”
Section: Discussionmentioning
confidence: 77%
“…Based on these data, use of these medications is likely to increase among cardiologists, and the coordination between cardiologists and PCPs when initiating and monitoring these medications will be critical. Additionally, influenza vaccination reduces the risk of secondary myocardial infarction in patients with CAD . However, this was the HEDIS measure with lowest achievement rates in our population.…”
Section: Discussionmentioning
confidence: 77%
“…We showed that the effectiveness of influenza vaccine as a coronary prevention of 15-45% against AMI, makes it comparable to accepted strategies such as smoking cessation (32-43% efficacy), use of statins (19-30% efficacy) and use of antihypertensive drugs (17-25% efficacy) [3]. A paradigm shift is required to view influenza vaccination as another available strategy for secondary prevention of AMI in addition to accepted measures such as statins.…”
Section: Cvd and Influenza Vaccinementioning
confidence: 99%
“…The pooled vaccine effectiveness against AMI calculated from all available studies is 29% [4]. From observational studies, it is estimated that influenza vaccine could provide vaccine effectiveness of 15-45% against MI [3,11]. In addition, the vaccine effectiveness is more evident in AMI patients with early seasonal influenza vaccination compared with midseason vaccination (21 vs 12%) in a large matched case-control study conducted in the UK [11].…”
Section: Cvd and Influenza Vaccinementioning
confidence: 99%
“…nation can contribute to a 15% to 45% reduction in acute coronary events. 5 The development of a vaccine for COVID-19 is of significant interest and a research priority. As we wait for this vaccine, developing strategies to reduce the likelihood of infection with COV-ID-19 will be critical for healthcare systems to protect vulnerable populations like cardiac patients during this surge of cases.…”
mentioning
confidence: 99%